The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1471-2180-14-156
|View full text |Cite
|
Sign up to set email alerts
|

Role IL-17A and IL-10 in the antigen induced inflammation model by Mycoplasma pneumoniae

Abstract: BackgroundMycoplasma pneumoniae is one of the causative organisms of community-acquired pneumonia which is found commonly in younger patients. Extrapulmonary complications similar to autoimmune disease are caused by M. pneumoniae following the initial infection. The mechanism and pathology of onset is not clear, but it is considered that excessive host immunoreactions play a part in the onset of mycoplasmal pneumonia and its extrapulmonary complications. In this study, we investigated the participation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 43 publications
(37 reference statements)
1
23
0
Order By: Relevance
“…In children with M. pneumoniae infection, the level of soluble intercellular adhesion molecule-1 is also markedly increased, which induces the increased bronchial reaction (61). M. pneumoniae antigens induce a potent immune reaction and enhance the Th17 cell response in vivo and in-vitro , with Treg and IL-10 being associated with the suppression of the production of IL-17A (62). The cytadherence of M. pneumoniae induces inflammatory responses through TLR4 and autophagy (6).…”
Section: Inflammatory Damagementioning
confidence: 99%
“…In children with M. pneumoniae infection, the level of soluble intercellular adhesion molecule-1 is also markedly increased, which induces the increased bronchial reaction (61). M. pneumoniae antigens induce a potent immune reaction and enhance the Th17 cell response in vivo and in-vitro , with Treg and IL-10 being associated with the suppression of the production of IL-17A (62). The cytadherence of M. pneumoniae induces inflammatory responses through TLR4 and autophagy (6).…”
Section: Inflammatory Damagementioning
confidence: 99%
“…In addition, IL‐17 also plays a key role in autoimmune diseases . Recently, it has been reported that the breakdown of the immune balance between T helper type 17 (Th17) cells and Tregs may be part of the process leading to the subsequent development of extrapulmonary manifestations . These findings indicate that IL‐17 may be involved in disease severity and extrapulmonary manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa [114] or understand the underlying mechanisms of pathogenesis, for example in case of M. pneumonia [115]. New vaccines against several pathogens including A. baumanii [107] or S. aureus [116] were studied in vivo. Reconstructed tissue models have shown many advantages compared to in vivo models.…”
Section: Pneumoniamentioning
confidence: 99%